Early controlled release of peroxisome proliferator-activated receptor β/δ agonist GW501516 improves diabetic wound healing through redox modulation of wound microenvironment - Choong, Cleo Swee Neo (2015)
Diabetic wounds are imbued with an early excessive and protracted reactive oxygen species production. Despite the studies supporting PPARβ/δ as a valuable pharmacologic wound-healing target, the therapeutic potential of PPARβ/δ agonist GW501516 (GW) as a wound healing drug was never investigated. Using topical application of polymer-encapsulated GW, we revealed that different drug release profiles can significantly influence the therapeutic efficacy of GW and consequently diabetic wound closure. We showed that double-layer encapsulated GW microparticles (PLLA:PLGA:GW) provided an earlier and sustained dose of GW to the wound and reduced the oxidative wound microenvironment to accelerate healing, in contrast to single-layered PLLA:GW microparticles. The underlying mechanism involved an early GW-mediated activation of PPARβ/δ that stimulated GPx1 and catalase expression in fibroblasts. GPx1 and catalase scavenged excessive H2O2 accumulation in diabetic wound beds, prevented H2O2-induced ECM modification and facilitated keratinocyte migration. The microparticles with early and sustained rate of GW release had better therapeutic wound healing activity. The present study underscores the importance of drug release kinetics on the therapeutic efficacy of the drug and warrants investigations to better appreciate the full potential of controlled drug release.